2017
DOI: 10.1016/j.watres.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Organic compounds in hydraulic fracturing fluids and wastewaters: A review

Abstract: High volume hydraulic fracturing (HVHF) of shale to stimulate the release of natural gas produces a large quantity of wastewater in the form of flowback fluids and produced water. These wastewaters are highly variable in their composition and contain a mixture of fracturing fluid additives, geogenic inorganic and organic substances, and transformation products. The qualitative and quantitative analyses of organic compounds identified in HVHF fluids, flowback fluids, and produced waters are reviewed here to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 170 publications
(74 citation statements)
references
References 79 publications
(224 reference statements)
3
71
0
Order By: Relevance
“…Of these hydrocarbons are a number of polycyclic aromatic hydrocarbons (PAHs), the most abundant being phenanthrenes, anthracenes, and naphthalenes that have been previously described in other work [39]. A pesticide, atrazine, was also found in a single sample (PW 3), albeit at low levels that corroborates the idea that pesticides in PW are at ultra‐trace levels and are rarely found in samples [13,40]. Many of these compounds, which given the abundance found in the samples analyzed, pose major environmental concerns due to their toxicity and persistence in the environment, most of which are supported by other works in the literature [14,39,40].…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Of these hydrocarbons are a number of polycyclic aromatic hydrocarbons (PAHs), the most abundant being phenanthrenes, anthracenes, and naphthalenes that have been previously described in other work [39]. A pesticide, atrazine, was also found in a single sample (PW 3), albeit at low levels that corroborates the idea that pesticides in PW are at ultra‐trace levels and are rarely found in samples [13,40]. Many of these compounds, which given the abundance found in the samples analyzed, pose major environmental concerns due to their toxicity and persistence in the environment, most of which are supported by other works in the literature [14,39,40].…”
Section: Resultssupporting
confidence: 71%
“…A pesticide, atrazine, was also found in a single sample (PW 3), albeit at low levels that corroborates the idea that pesticides in PW are at ultra‐trace levels and are rarely found in samples [13,40]. Many of these compounds, which given the abundance found in the samples analyzed, pose major environmental concerns due to their toxicity and persistence in the environment, most of which are supported by other works in the literature [14,39,40]. Most notably is the constituent 1,4‐dioxane, a previously discovered PW component that is associated with human cancer [13,23] and has been shown to be challenging to remove from the waste‐stream [23].…”
Section: Resultssupporting
confidence: 67%
“…However, to date, only 238 owback and produced samples have been analyzed to identify specic organic compounds in the published literature. 2 This small number of analyses have included inorganic [11][12][13][14][15][16][17] and organic 2,18-25 components of owback water, but the vast well-to-well diversity (spatially and temporally 13,21 ) and comparably complex suites of disclosed additives 26,27 pose massive hurdles for complete characterization at the eld's current pace. In particular, a high degree of uncertainty remains regarding the nature of anthropogenic additives themselves and their capacities to persist or transform in the subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…Industrial ingredient reports have been disclosed through FracFocus, 36 a publicly available online database, and by the United States Congress. 37 Generally, these chemicals serve a wide array of purposes to optimize hydraulic fracturing operations, 26 from (1) controlling the chemical environment within wells to prevent degradation (e.g., biocides and scaling inhibitors) to (2) altering the uid's physicochemical properties in situ. 26,27 Equipped with an understanding of subsurface conditions, 38 researchers have simulated the shale well parameter space in laboratory systems to interrogate and characterize subsurface reaction pathways, demonstrating conditions or additives that can either mitigate or encourage transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Limited characterization studies of produced water have identified nearly 600 chemicals in produced water associated with hydraulic fracturing (USEPA ). More recent studies using high‐resolution mass spectrometry indicate that the number of potentially detectable chemicals may be much greater (Hoelzer et al ; Luek and Gonsior ; Luek et al ; Piotrowski et al ).…”
Section: Introductionmentioning
confidence: 99%